LEAF AREA INDEX OF BLACK LOCUST STANDS IN NORTHERN STEPPE OF UKRAINE - Sytnyk, S. A.; Lakyda, P. I. (Forestry and Forest Melioration, 2018)
Introduction The leaf area index (LAI) of forest ecosystems is the subject of modern investigation in Ukraine and the world. In the forest plantation within Northern Steppe, locust tree (Robinia pseudoacacia L.) stands area is 17,683.7 hectares (26.9 % of the total forest covered area in Dnipropetrovsk region). The goal of this research is to determine values of LAI for black locust stands in the forest plantations within Northern Steppe of Ukraine. Materials and methods The article presents biometric characteristics of temporary sample plots and trees, a method for determining the structural elements of LAI and results of leaves weight depending on the surface area. The relationships between the weight of leaf samples in fresh and absolutely dry conditions and the age of the model trees were analyzed. The ratio of fresh and dry weight to the total surface area of leaf samples was calculated, and its average value was found. Leaf surface area of black locust stands was determined on the temporary sample plots Sampling technique for weight determination of leaf fraction with established surface area was that the leaves were separated from selected model branches of model trees and the leaf samples were taken by using a hand probe tools. As experimental material we have used experimental data from five temporary sample plots with a cutting of 15 model trees which were laid out in pure and mixed black locust stands in Northern Steppe of Ukraine in Dnipropetrovsk region. The temporary sample plots represented different age groups and had high and medium productivities. The stands grew in in dry and fresh fairly fertile and dry fertile oak forest type conditions by Pohrebnyak’s classification. Results We calculated that the overall average index of leaf surface area for black locust stands of the Northern Steppe of Ukraine was 4.55. For young (10-year-old) stands, LAI was close to the minimum value and was in the range of 2.27–2.91 m? per m?. The maximum value of LAI (11.03 m? per m?) corresponds to the forest stand of 36 years old, which is the age of maturity for black locust stands in the Ukrainian steppe zone. Conclusions The mass of leaf samples from the leaves of black locust depends on the age of the model trees, which affects the ratio of the mass of leaves to their area. The leaf area of locust stands depends on the type of forest site condition and the age of the stands. 1 Fig., 4 Tables, 9 Refs.